(untitled) (MAUSAM, 1981)
Utilising monthly normals of daily maximum and minimum temperature and their corresponding relative humidity for 223 stations distributed over India, Comfort Indices CS (Annual Cummulative Stress), PCS (Proportional Cumulative Stress), APR (Annual Physioclimatic Regime) have been computed and the geographical classification of physioclimatic regimes over India on the basis of the above comfort indices has been discussed. The practical utility of the classification has also been mentioned.